2009
DOI: 10.1111/j.1365-2443.2008.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Retroendocytosis pathway of ABCA1/apoA‐I contributes to HDL formation

Abstract: ATP-binding cassette protein A1 (ABCA1) mediates transfer of cellular free cholesterol and phospholipids to apolipoprotein A-I (apoA-I), an extracellular acceptor in plasma, to form highdensity lipoprotein (HDL). It is currently unknown to what extent ABCA1 endocytosis and recycling contribute to the HDL formation. To address this issue, we expressed human ABCA1 constructs with either an extracellular HA tag or an intracellular GFP tag in cells, and used this system to characterize endocytosis and recycling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 40 publications
6
64
1
Order By: Relevance
“…Because the expression levels of ABCA1 were kept very low (<0.3 copies/μm 2 ) for singlemolecule imaging in the present study, we observed very limited numbers of oligomer-like bright spots before apoA-I application. The interconversions of ABCA1 between dimers and monomers observed here occurred on the PM, likely to be independent of the endocytic pathway (30,31). The observation that an ATPasedeficient ABCA1 mutant, ABCA1-MM, which is unable to generate HDL, did not form dimers or show immobilization on the PM implies an obvious medical impact that dimerization of ABCA1 is physiologically critical.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Because the expression levels of ABCA1 were kept very low (<0.3 copies/μm 2 ) for singlemolecule imaging in the present study, we observed very limited numbers of oligomer-like bright spots before apoA-I application. The interconversions of ABCA1 between dimers and monomers observed here occurred on the PM, likely to be independent of the endocytic pathway (30,31). The observation that an ATPasedeficient ABCA1 mutant, ABCA1-MM, which is unable to generate HDL, did not form dimers or show immobilization on the PM implies an obvious medical impact that dimerization of ABCA1 is physiologically critical.…”
Section: Discussionmentioning
confidence: 73%
“…The dye:protein ratio was calculated to be between 2.5 and 5.0 by measuring the absorbance at 280 and 601 nm. Alexa546-apoA-I was prepared as previously described (30).…”
Section: Methodsmentioning
confidence: 99%
“…Substitution of the C-terminal valine in the PDZ binding motif (13) Co-localization of LXR␤ and ABCA1 on the Plasma Membrane-To better characterize the interaction of LXR␤ with WT and mutant ABCA1, we examined the localization of ABCA1(207HA), a construct bearing an HA tag between residues 207 and 208 within the first extracellular domain, by confocal microscopy. Insertion of this HA tag does not affect apoA-I binding (22,23), cholesterol efflux (22,23), internalization (22,23), or the interaction with LXR␤ (data not shown). HEK293 cells stably expressing FLAG-LXR␤ were transiently transfected with ABCA1(207HA) (Fig.…”
Section: Leucine Residues Of Abca1 Mediate Its Interaction Withmentioning
confidence: 99%
“…This peptide insertion had no effect on the subcellular localization or the function of ABCA1. 17) The relative surface expression of each mutant was calculated by dividing HA immunofluorescence by GFP fluorescence, and was compared with that of wild-type ABCA1 ( Fig. 1(B)).…”
Section: Resultsmentioning
confidence: 99%